The second sister - Kendal, Claire (London HarperCollins Publishers, 2017)
The chilling new psychological thriller by Claire Kendal, author of the bestselling novel, THE BOOK OF YOU, which was selected for Richard and Judy in 2015. Perfect for fans of THE GIRL ON THE TRAIN and DISCLAIMER. Ten years ago, Ella's sister Miranda vanished without trace. Now thirty, the same age as Miranda when she disappeared, Ella has grown to look dangerously like the missing woman. Ella becomes convinced that the man who took Miranda is watching her family. To Ella, this is an opportunity as much as a prospect of fear. It makes her more determined than ever to find out what happened to the beautiful and mysterious Miranda. Because who better than a sister to see what the police overlooked and to understand the missing woman? Especially as the perpetrator leaves new evidence that only Ella takes seriously. Is Ella paranoid, or intensely intuitive? She idolised her older sister, but now she will need to face some difficult truths. How was Miranda, a nurse, able to pay cash for her flat and her luxury car? What made her write a will when she was still pregnant, asking that custody of her child be shared between Ella and her parents? The price of learning Miranda's fate will be far higher than Ella imagines
1
Keywords: Family secrets; Missing persons -- Fiction; Missing persons; Secrets -- Fiction; Sisters -- Fiction; Sisters; Fiction; Psychological fiction; Psychological fiction; Psychological fiction; Suspense fiction; Thrillers (Fiction); Thrillers (Fiction)